PEMBANGUNAN SEKTOR PERTANIAN SEBAGAI UPAYA PENINGKATAN PEREKONOMIAN KABUPATEN SUMBAWA - Heru Surahmad; A Asmini; K Kamaruddin (Jurnal Ekonomi & Bisnis, 2023)
This study aims to analyze the agricultural sector development strategy as an effort to improve the economy in Sumbawa District. This study used a descriptive method with a qualitative approach. The type of data used in this study is qualitative data in the form of research informants' perceptions regarding agricultural sector development strategies as an effort to improve the economy of Sumbawa District obtained through interviews. Informants in this study were determined using a purposive technique, namely determining informants based on certain criteria. The informants for this study consisted of the Head of the Agriculture Department, the Head of UPTD. Untir Iwes Sub-District, rice farmers and corn farmers. Data analysis in this study used the SWOT analysis technique. The results of this study showed that the SWOT analysis of agricultural sector development as an effort to improve the economy in Sumbawa District produces four alternative strategies, namely SO Strategy, ST Strategy, WO Strategy, and WT Strategy. In general, the results of this study describe that the agricultural sector in Sumbawa District has enormous potential to be developed as an effort to improve the economy in Sumbawa District. The priority of the agricultural sector development strategy as an effort to improve the economy in Sumbawa District is to increase the government's active role in the development of the agricultural sector and to collaborate with related agencies to design a program to accelerate the development of the region's leading agricultural sector.